Empowering Coastal Women through Alternative Livelihoods - Budiman Budiman; Dwi Agna Withri; Al Furkan; M. Said Ramdlan; Rusmin Nuryadin; Abdul Gafur (Unram Journal of Community Service, 2026)
Coastal communities are among the most vulnerable groups affected by climate change due to inconsistent fish catches, increasing operational cost of fishermen, changing weather patterns, and increasing long-term economic uncertainty. These challenges directly affect household livelihoods, particularly those reliant on small-scale fisheries. This community empowerment program aimed to strengthen the adaptive capacity of coastal women by developing alternative livelihoods through fishery-based processed products. The program was implemented in Senteluk and Meninting Villages, West Lombok Regency, Indonesia, involving 30 women organized into three community groups within one year period, from March 2024 to February 2025. Activities included participatory planning, focus group discussions, capacity-building workshops, practical training in fish processing, packaging and branding, financial management, digital marketing, and business legalization assistance. The program successfully established three legally recognized women's groups, delivered twelve capacity-building workshops, developed three fishery-based products (abon ikan, stik ikan, and kacang ikan), and facilitated the acquisition of initial business legalization, food safety certification, and halal certification. Social media platforms among participants were utilized as medium support for product marketing. The initiative demonstrates that community-based women's empowerment, combined with local resource utilization, can strengthen household economic resilience while contributing to climate change adaptation strategies in coastal settings.